2001
DOI: 10.1074/jbc.m106967200
|View full text |Cite
|
Sign up to set email alerts
|

N-end Rule Specificity within the Ubiquitin/Proteasome Pathway Is Not an Affinity Effect

Abstract: The N-end rule relates the amino terminus to the rate of degradation through the ubiquitin/26 S proteasome pathway. Proteins bearing basic (type 1) or large hydrophobic (type 2) amino termini are assumed to be targeted through this pathway by their higher affinity for binding to the responsible E3 ligase compared with proteins bearing other residues (type 3). Paradoxically, a significant fraction of eukaryotic protein degradation occurs through the N-end rule pathway, although the majority of cellular proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 61 publications
0
47
1
Order By: Relevance
“…This conclusion, based on the authors' interpretation of their enzymological evidence (29), is directly in conflict with both the earlier UBR1-binding data (6) and the results above. The technically straightforward, catalysis-free binding assays with yeast and mouse UBR1 (Fig.…”
Section: Specificity Of Ubr1 Interactions With Cup9 and Ligands Bearingcontrasting
confidence: 56%
See 1 more Smart Citation
“…This conclusion, based on the authors' interpretation of their enzymological evidence (29), is directly in conflict with both the earlier UBR1-binding data (6) and the results above. The technically straightforward, catalysis-free binding assays with yeast and mouse UBR1 (Fig.…”
Section: Specificity Of Ubr1 Interactions With Cup9 and Ligands Bearingcontrasting
confidence: 56%
“…Recently, Baboshina et al (29) suggested that the mammalian N-end rule pathway distinguishes between stabilizing and destabilizing N-terminal residues not through differences in the thermodynamic affinities of UBR1 (E3␣) for these residues, but largely through differences in the catalytic activity of UBR1 in response to its (comparably avid) binding to either stabilizing or destabilizing N-terminal residues. This conclusion, based on the authors' interpretation of their enzymological evidence (29), is directly in conflict with both the earlier UBR1-binding data (6) and the results above.…”
Section: Specificity Of Ubr1 Interactions With Cup9 and Ligands Bearingmentioning
confidence: 99%
“…4A). The latter control additionally confirms that the assays contain sufficient Uba1 to maintain all Ubc5A charged as the corresponding Ubc5A-125 I-ubiquitin thioester, the actual substrate for TRIM32 (33,49). Excision of the lanes from the gel and quantitation of the associated radioactivity by ␥-counting allows one to calculate the corresponding rate of polyubiquitin chain formation based on the specific radioactivity of the 125 Iubiquitin (10,32,49).…”
Section: Conservation Of E2 Specificity Within the Trim Ligasementioning
confidence: 87%
“…In line with these reports, we show that in vitro E2D can utilize both Lys 48 and Lys 63 in polyubiquitination. A broader range of lysine specificity was detected when the Rad6 (E2A/B) was used in polyubiquitination with various E3s (Bre1, Ubr1, and Rad18) (20,34,45), each selecting different lysine specificity from the potential conjugation abilities of Rad6 (Lys 11 and Lys 48 ). In aggregate, the clear overlap in the lysine preferences demonstrated by a given E2, independent of the presence or absence of an E3 enzyme, is a strong indicator of the central role of the E2 enzymes in the determination of the lysine preference in ubiquitination.…”
Section: E2 Enzymes Have a Role In Determining The Lysine Preferencementioning
confidence: 99%